The influence of back squats in combination with reactive strength training or strength training of the plantar flexors on speed and jump performance in youth elite soccer players - Kadlubowski, B.; Keiner, M.; Wirth, K.; Csapo, R. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Soccer, characterized by dynamic movements like sprinting, jumping, and directional changes, heavily relies on explosive actions for scoring goals [1]. One crucial factor in facilitating rapid force development during these actions is the stretch-shortening cycle [2]. Despite numerous studies investigating training interventions to enhance speed and jumping ability in soccer players, there is still a gap in our under-standing regarding the effectiveness of isolated plantarflexor muscle strength training [3]. This study aimed to compare the effects of combined training interventions incorporating back squats with either calf raises or plyometric training, on the linear sprint and jump performance of youth soccer players. METHODS: A longitudinal six-month training study was conducted with male youth soccer players (n = 89) from two elite youth training centers in Germany. Participants were divided into two intervention groups (PLY-BS, plyometric exercises + back squat; CR-BS, back squat + calf raises), and a control group (CG), which per-formed the conventional soccer-specific training only. Outcome measures included back squat and calf raise one-repetition maxima (1-RM), linear sprint times (5m, 10m, 30m) as well as the performance in countermovement jumps (CMJ) and drop jumps (DJ) from heights of 15cm, 30cm, 45cm, and 60cm. RESULTS: A mixed factorial ANOVA showed that 5m LS times were affected by time (p